Analysis of microstructure and mechanical properties of micro‑plasma arc‑welding‑based additive manufacturing - Rosli, Nor Ana; Alkahar, Mohd Rizal; Paijan, Lailatul Harina; Abu Bakar, Mohd Hadzley; Mohamad Norani, Mohamad Nordin (Springer Nature, 2024)
Wire arc additive manufacturing (WAAM) is an emerging additive manufacturing (AM) process that gained considerable interest due to its high deposition rate and fexibility in build scales. Low heat input, reduced thermal gradient, refned grains structure and optimal molten pool are required in producing more high-quality WAAM parts. Integrating a microplasma arc welding (MPAW) system with less or equal to 20A current is a signifcant consideration in WAAM technology to improve its quality. This study fabricated a single-pass multilayer structure with MPAW-based WAAM, and the efect on macro–microstructure and tensile strength has been thoroughly investigated. The results show that excessive heat at the end of layer deposition leads to deteriorated structure and irregular geometrical shapes. Owing to the WAAM process that experiences repeated heating and cooling, the bottom structure has the highest tensile strength and microhardness due to the fne dimple structure form. The observed microstructure shows that the grain size at the top wall is larger than that at the bottom due to more rapid cooling at the bottom. Based on the study outcome, the study provides a better understanding of the morphological, microstructure, and mechanical properties of samples fabricated using MPAW-based WAAM process.